(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
كما أفاد تحليل صور الأقمار الصناعية من النوع SST في فهم وتوصيف حركة الكتل المائية في الحوض الشرقي للمتوسط وأظهر خصائص كثيرة للعديد من الدوامات البحرية فإننا في هذا البحث نسلط الضوء على أهمية هذا النوع من الصور في الكشف عن ظاهرة الـ upwelling في الحوض الشرقي للمتوسط لما لها من انعكاسات بيولوجية هامة على البيئة البحرية. تم في هذا البحث الاعتماد على صور تعود لفترات مختلفة بهدف الإشارة إلى أماكن وجود الظاهرة وهذا سيكون بمثابة البوصلة التي ستشير إلى أماكن الاعتيان بغية دراسة المغذيات التي تعد أساس السلسلة الغذائية الأولى. SST satellite images analysis has provided us a new description of the surface circulation in the eastern basin of the Mediterranean Sea. It showed many characteristics for a lot of mesoscale eddies. In this study, the SST analysis is focalised on the upwelling structure showing by images, in the eastern basin of the Mediterranean Sea, which has an important biological reflection at the marine environment. We have analyzed images for different periods to identifier this phenomena’s places and this will be help us in situ nutrient observations.